"I am not a friend to men": Embodiment and desire in Magnus Hirschfeld's Transvestites case studies. Issue 2 (3rd April 2018) - Heaney, Emma
ABSTRACT: This article reads sexological case studies of the fin-de siècle that contain accounts of trans women's lives in the period. It argues that these sources contradict the diagnostic criteria that doctors determine as the factors that define trans feminine identity in the period: desire for men, social isolation, and tortured bodily dissatisfaction. Chief among these contradictions is the prevalence of the expression of trans women's desire for women and easy participation in women's social and kinship networks. Therefore, this article considers these narratives to be a crucial and overlooked resource for considering the breadth of lesbian identity and sociality in the late nineteenth and early twentieth century.